2018
DOI: 10.18632/oncotarget.25002
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume as a predictive marker for venous thromboembolism in patients treated for Hodgkin lymphoma

Abstract: Mean platelet volume (MPV) is reported to be associated with the risk of venous thromboembolism (VTE) and mortality in patients with cancer.We sought to determine the association of MPV with symptomatic VTE occurrence in patients treated for newly diagnosed Hodgkin lymphoma (HL) and their outcomes. We retrospectively studied 167 consecutive adult patients treated with HL. During first-line treatment 12 (7.2%) patients developed VTE and 14 (8%) died within the observation period. The pre-chemotherapy values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 54 publications
2
18
0
1
Order By: Relevance
“…Our study is the first to show that a high MPV is a predictor of poor outcomes in patients with NHL and HIV, even controlling for IPI and histological subtype of lymphoma. These results are similar to those reported by Rupa-Matysek in patients with Hodgkin's lymphoma, who found a trend to better survival in patients with low MPV (<6.8 fL), although this finding did not reach statistical significance (log rank test =1.124, p =0.2610) [33]. However, our results are opposite to what Rupa-Matysek et al reported in patients with diffuse large B-cell lymphoma and without HIV.…”
Section: Discussionsupporting
confidence: 75%
“…Our study is the first to show that a high MPV is a predictor of poor outcomes in patients with NHL and HIV, even controlling for IPI and histological subtype of lymphoma. These results are similar to those reported by Rupa-Matysek in patients with Hodgkin's lymphoma, who found a trend to better survival in patients with low MPV (<6.8 fL), although this finding did not reach statistical significance (log rank test =1.124, p =0.2610) [33]. However, our results are opposite to what Rupa-Matysek et al reported in patients with diffuse large B-cell lymphoma and without HIV.…”
Section: Discussionsupporting
confidence: 75%
“…Another emerging parameter is the mean platelet volume (MPV) [42,43]. A lower MPV has been associated with the risk of VTE in cohorts of patients with DLBCL and HL, however, with varying cut-points [44,45].…”
Section: Laboratory Variablesmentioning
confidence: 99%
“…Patients with baseline MPV 6.8 fL or below more often developed VTE compared to patients with higher MPV values (19% vs. 5.5%, p = 0.0244). Of the HL patients, in both the univariate and multivariate models, the patients with baseline low MPV levels had an above twofold increased risk of VTE development [29].…”
Section: Prognostic Value Of Mpv In Lymphoproliferative Diseasesmentioning
confidence: 99%